Analisis Perbandingan Metode Simple Queue dengan PCQ dan Queue Tree dengan PCQ dalam Manajemen Bandwidth (Studi Kasus: MTsN 8 Banyuwangi) - Evi Hidayatun Nafiah (Fakultas Ilmu Komputer, 2024)
The Internet is one of the information technologies that has significantly influenced various aspects of human life. MTsN 8 Banyuwangi is one of the junior high schools that has provided internet access to support the education service process. The available internet network often faces challenges such as unstable and slow connections when used simultaneously. These issues arise from the high number of users with different internet needs in each room, without bandwidth restrictions for individual users. Considering these conditions, bandwidth management is needed to enhance the efficiency of the available internet network using the Simple Queue method with PCQ and Queue Tree with PCQ. Both methods will be compared to determine which one is better suited for implementing bandwidth management at MTsN 8 Banyuwangi. The comparison of the two methods is conducted by calculating Quality of Service (QoS) values for several parameters, namely throughput, delay, jitter, and packet loss. Testing these parameter values uses the Wireshark application and manual calculations to obtain QoS values in accordance with TIPHON standards. The results of this research indicate that the Queue Tree method with PCQ has better performance in simulating bandwidth management on the internet network at MTsN 8 Banyuwangi compared to the Simple Queue method with PCQ. The throughput deviation value in the Queue Tree method with PCQ is lower by 356.2302 compared to the Simple Queue method with PCQ, which is 566,7029. Furthermore, other QoS parameters such as packet loss, delay, and jitter also show better results in the Queue Tree method with PCQ, with values of 0.39%, 6.46 ms, and 6.46 ms, respectively. In comparison, the Simple Queue method with PCQ has higher QoS parameter values, namely 0.45%, 6.94 ms, and 6.94 ms.
Reuploud Repository hasyim Juni 2026 :: Finalisasi Repositori File 3 Juni 2026_Kurnadi
Keywords: Simple Queue; Queue Tree; Per Connection Queue (PCQ); Bandwidth Management